PSYCHOPATHY: MYTH OR CRAZY REALITY? (Psychology Travelogs, 2023)
Over the past few years, there has been a growing interest in researching and understanding psychopathy. This is mainly due to the fact that there has been an increase in the number of cases where individuals exhibit personal anomalies, leading to various behavioral disorders and causing significant damage to social interactions. These disorders not only cause immense harm to the individual but also create negative impacts on the social environment, including their family, friends, and colleagues. The main goal of this study is to study such a personality disorder as psychopathy. The article briefly presents a historical analysis of the emergence and development of the concept of “psychopathy”. When researching this issue, a survey was conducted, and the following scientific methods were used: structural-functional and dialectical methods, the method of synthesis, logical and comparative analysis, and the method of generalization. The main task of this study is the study of etiology, analysis of characteristic signs, symptoms of psychopathy, as well as the study of classification according to the International Classification of Diseases of the tenth and eleventh revisions, and based on this, to highlight what is really related to psychopathy, and which representations are stereotyped. The results of this study are a detailed analysis of psychopathic personality disorder, as well as confirmation that psychopathy exists today, but the understanding, definition, and even the name have changed. The practical significance of this work is that all theoretical provisions, conclusions and recommendations can be used in educational institutions by teachers and students to improve knowledge about such a psychological feature of a person as psychopathy, as well as by other scientists for a more detailed study of this psychological disorder.
Keywords: psychological disorder; disharmonization; mental illness; personality disorder; individual